PENATALAKSANAAN NYERI PASCA SECTIO CAESAREA PADA IBU POSTPARTUM MELALUI ASUHAN KEPERAWATAN: STUDI KASUS - Mariana Oni Betan; Antonia Helena Hamu; Febtian C. Nugroho; Maria Agustina Making; Roswita V. Rambu Roku; Benedicta Udju Moro Mauday (Bajang Institute, 2026)
Background: Postoperative pain following cesarean section is one of the most common problems experienced by postpartum mothers due to tissue trauma and the inflammatory process after surgery. Inadequately managed pain may hinder early mobilization, disrupt rest and sleep, reduce comfort, and delay postpartum recovery. Therefore, comprehensive nursing care is needed to manage pain effectively in post-cesarean patients. Objective: To describe nursing care for a postpartum patient experiencing acute pain following a cesarean section. Methods: This study employed a descriptive case study design using the nursing process approach. The subject was one postpartum patient who underwent a cesarean section and was hospitalized in the Flamboyan Ward of RSUP Ben Mboi. Data were collected through interviews, observations, physical examinations, medical record reviews, and pain assessment using the Numeric Rating Scale (NRS). Nursing care was implemented for 3 × 24 hours. Results: The assessment revealed that the patient experienced acute pain at the surgical incision site with a pain score of 7 on the NRS, accompanied by sleep disturbances and limited mobility. The nursing diagnosis established was acute pain related to physical injury agents secondary to surgery. Nursing interventions included pain management, deep-breathing relaxation techniques, cold compress application, environmental modification, gradual mobilization, patient education, and collaboration in analgesic administration. After 3 × 24 hours of nursing care, the patient's pain intensity decreased from a score of 7 to 3, accompanied by improved comfort and increased ability to perform daily activities. Conclusion: Nursing care based on comprehensive pain management was effective in reducing pain intensity, improving patient comfort, and supporting recovery in a postpartum patient following cesarean section.